Studies on public health and hygiene condition of retailers at fish markets in south-central Bangladesh (Journal of the Bangladesh Agricultural University, 2016)
Bangladesh is a fish producing country from the ancient history due to its deltaic nature agro-ecologically. Accordingly fish marketing systems developed in traditional systems sincelong. This study was conducted in two retail fish markets located in Rajbari and Barisal Sadar Upazila in the south central region of Bangladesh focusing public health and hygiene condition of retailers. The questionnaire interview with 30 retailers and participatory rural appraisal (PRA) tools were used to get the information from the retailers and other value chain stakeholders. About 13% of the retailers had no education, however 60% had primary level and 27% had secondary level of education. Although many of them were literate, their knowledge and practice about public health, hygiene and sanitation was found to be very poor. Due to lack of knowledge on public health, they were found to be infected by various contagious diseases such as common cold (cough, coryza etc.), diarrhoea, lesion (lesion on hands, between fingers, on the tip of the fingers, between toes, on the nail and tip of the toes etc.) and skin disease. About 57% of them were affected with lesion on hands, while 33, 23, 7, 13 and 10% were affected with lesion between fingers, between toes, on the tip fingers, on the nail and tip of toes and skin disease on legs, respectively.Fish markets operated by them were ill-managed, unhygienic and unscientific. So, the hygiene and sanitation system of retail fish markets were very poor and unhealthy. Market should have adequate water supply, toilets and other sanitation facilities. Due to poor infrastructural facilities in harvest and post-harvest, landing, handling, preservation, distribution, marketing and quality assurance, the fish retailers suffered from serious health problems. Good personal hygiene management is therefore essential for the safe handling and preparation of fish and fisheries products. To ensure this, quick and proper action should be needed by the government, particularly by the local government and rural development (LGRD) authorities.J. Bangladesh Agril. Univ. 12(2): 411-418, December 2014